Analytic Study of Information Functions: Management Information System Transformation at MAN 2 Yogyakarta - Ananda Amalia Romadhona; Ahmad Kamal Assidiqi; Tiara Nur Urbiyanti; Daffa Alif Umar Himawan; Sumarsono (Proceeding International Conference on Religion, Science and Education, 2023)
The development of information technology has an impact on educational institutions. Effective and modern management information systems are the main academic domain so that learning objectives are achieved. One of them is updating digital applications as a form of excellent madrasah service in maximizing learning. In improving the efficiency of school management services, MAN 2 Yogyakarta utilizes the information function through the use of an effective and modern management information system. The purpose of this study was to determine the effect of management information systems on learning effectiveness by identifying specific variables at MAN 2 Yogyakarta in the form of information systems that have been continuously developing for more or less the last 10 years. The results show that these variables are elevators of the overall information. The purposive sampling method was used in selecting respondents who were the research sample. The results show that this sample of participants contributes to the total of all information. Data collection used standard audio recordings to record interviews and all interviews were fully verbally transcribed by several respondents. Data were collected using in-depth observation, in-depth interviews, and documentation. The first method collects demographic information about respondents by interviewing. Data were analyzed using data reduction, data display, and conclusion drawing or verification. The data is then analyzed, categorized, and interpreted into themes and sub-themes that emerge through coding. The results show excellent service through management information systems and efficient implementation of service technical tasks, as well as very effective technology and information in student learning.